Assessing external effects of city airports: land values in Berlin - Gabriel M. Ahlfeldt; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2008)
This paper employs a hedonic price model to explain standard land values in Berlin. Impact on land values is assessed for the two city airports situated in Berlin, Germany, Tempelhof and Tegel. Empirical results confirm expectations about the impact of various attributes on land values. Areas exposed to noise pollution of downtown airport Tempelhof sell at a discount of approximately 5-9% within a distance of 5000 m along the air corridor. No significantly negative impact was found for land values around Tegel Airport, which is located in a central, but less densely populated, area. Market access indicators created for all three Berlin airports in operation, including Berlin Schoenefeld International Airport, reveal clear location advantages in terms of accessibility of Tempelhof and Tegel compared to Schoenefeld Airport, where the new Berlin Brandenburg International Airport is about to be developed.
Keywords: R31; R42; R53; 330; Air Traffic; Land Values; Airport; Hedonic Regression; Berlin